Strengthening School-University Partnership through ‘Lesson Study’ in School Internship - Rastogi, Anita; Sandhya Vaid (JOURNAL OF INDIAN EDUCATION, 2022)
School-university partnership is gaining momentum for the preparation of prospective teachers. The authors are of the view that lesson study, with its proven effectiveness in other countries, can be adapted and followed in the school internship of pre-service teacher education programmes in India. It can go a long way in strengthening the partnership between the school and teacher education institutions, which at present is just ornamental. It would lead to a win-win situation for both by equipping the prospective teachers with the skills to handle the real classroom situations effectively under the mentorship of school teachers and facilitating the school mentors in their professional growth with the shared focus on school students’ learning. The seeds of sustainable professional development could also be sown among prospective teachers during school internship through the adoption of lesson study practices. Against this backdrop, the authors have suggested an adapted model of lesson study and conditions for its success in India.